Por um ensino significativo da dança - Maria Graziela Mazziotti Soares da Silva; Gisele Maria Schwartz (Universidade Federal do Rio Grande do Sul, 2000)
This research, which has a qualitative characteristic, aimed to reflect on the parameter that envolves dance teaching. It focused some elements such as pedagogical practice, planning, objectives formulation, contents and adequated strategies elaboration, psychomotor aspects envolved in dance teaching, and the professionall characteristics, which are intervenient factors to reach an effective learning and to maximize the signif icant pedagogical perspectives.